PAINEL GLOBAL DE ESTUDOS DOS DETERMINANTES DO CRESCIMENTO DA GERAÇÃO DE ENERGIAS RENOVÁVEIS NO PERÍODO COMPREENDIDO ENTRE 2001 E 2 - Chiappori, Dino Vannucci (2015)
This dissertation provides an analysis related to the generation and consumption of renewable energy front of the fossil energy, taking as parameters the GDP per Capita GDP and other economic indicators as elements for analysis. It was studied the relationship between the development of nations, economic values, energy consumption, sustainability and greenhouse gases. Under this viewpoint seeks to understand and analyze how one may interfere in mitigating forms in favors to nature, for the benefit of this civilization. How and what renewable energy can affect the reduction of greenhouse gases, accelerating the decline in the use of fossil fuels For that is performed an analysis in generation and consumption of energy (fossil, renewable and other sources) panel, aggregate with economic indicators, in the context of ten years and at the level of all countries that account for data generation and power consumption used, as well as economic indicators used in this study. As a result ,in the decade, It was observed growth of GDP per capita, consumption of fossil energy, CO2 emissions and primary energy. It was noted strong growth of renewable energy, with significance for biofuels, solar, wind, biomass. The lower growth occurring in nuclear. Concluding that becomes urgent actions, globally, to increase up, exponentially, the generation of renewable and clean energies, with consequent reduction in the consumption of fossil fuels, exponentiating the generation of renewable energy and eradicating fossil fuels always where and when feasible.